Integrated and Sustainable Management of Post-industrial Coasts - Bardos, Paul; Spencer, Kate L.; Ward, Raymond D.; Maco, Barbara H.; Cundy, Andrew B. (Frontiers in Environmental Science, 2020)
The sustainable management of post-industrial coasts is a major emerging issue globally. Along such coasts, there may be a significant legacy of both contaminated land (including historic landfills and non-managed waste disposal) and contaminated sediments in and around urban and industrial areas, which require new strategies for cost-effective and integrated risk management under future sea-level rise and climate change scenarios. Here, we review current approaches to managing contamination in post-industrial coastlines, discuss emerging integrated management strategies (building on low input approaches to sustainable brownfields regeneration) and present an approach and framework for assessing and comparing different scenarios for coastal brownfield regeneration to soft re-use and other end-points. This framework can be applied to explore the opportunities for synergy and realisation of wider environmental, economic and societal benefits between coastal protection, dredged material re-use and the management of brownfield land. As such, the approach we propose supports planning and options appraisal to realise maximum benefit and value from integrated coastal management strategies.